Impressões e lutas dos trabalhadores gráficos de Fortaleza (1970 a 2000) - Araújo, Leo Natanael de Jesus (2014)
Industrial production of the printed word has undergone technological changes that culminated in the demise of the traditional crafts of typography and linotype. To understand these modes do, feel and represent the printed word appealed to the orality of compositors and typesetters through their testimonials. The narratives of the new printers and professional offset phototypesetting technology provide the questioning of the limits and possibilities of working-class struggle against capitalist exploitation, posed by this new world of work in the printing industry of Fortaleza. Multiple temporalities worked by his memories represent the experiences of these workers in the struggle against the subordination of labor to a capitalist logic of industrialism. Apart from oral sources, the documentary corpus is composed by union sources (meeting minutes, pamphlets, newspapers), reports and industry surveys of FIEC and SENAI, photographs, images, and specialized works in graphic production. The analysis was sustained on the theoretical contributions of the Social History of Labour (mainly EP Thompson), the Oral History Alessandro Portelli and the critique of industrialism Kirkpatrick Sale, plus a host of other authors.